1990
DOI: 10.3109/09513599009030689
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine profile associated with estrogen and progesterone receptors in leiomyoma and normal myometrium

Abstract: In leiomyoma and normal myometrium estrogen receptors act independently at low or high levels of the normal serum steroid range in the menstrual cycle. It might be an inherent characteristic of leiomyomas, which results in their progressive growth in the absence of any abnormal stimulation. In the secretory phase of the menstrual cycle, serum progesterone suppresses estrogen receptor concentrations in leiomyoma. In the present study serum follicle-stimulating hormone (FSH) and luteinizing hormone (LH) showed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Also the relation between these receptors seems to differ with a higher ER/PR ratio in leiomyomas than in myometrium (2). Accumulating evidence indicates that whereas elevated levels of progesterone down-regulate the estrogen receptor, estrogen may up-regulate the progesterone receptor in the human uterus (2,15,16). The functions of estrogen and progesterone in uterine smooth muscle cells might be complementary, with estrogen priming as a prerequisite for the optimal stimulation of proliferation by progesterone.…”
Section: Discussionmentioning
confidence: 99%
“…Also the relation between these receptors seems to differ with a higher ER/PR ratio in leiomyomas than in myometrium (2). Accumulating evidence indicates that whereas elevated levels of progesterone down-regulate the estrogen receptor, estrogen may up-regulate the progesterone receptor in the human uterus (2,15,16). The functions of estrogen and progesterone in uterine smooth muscle cells might be complementary, with estrogen priming as a prerequisite for the optimal stimulation of proliferation by progesterone.…”
Section: Discussionmentioning
confidence: 99%
“…The concept that progesterone suppresses the ER in fibroid tissue is further supported by the findings of Sadan et al (5), who found an inverse correlation between serum progesterone levels and fibroid ER concentration, using a ligand binding assay. The concept that progesterone suppresses the ER in fibroid tissue is further supported by the findings of Sadan et al (5), who found an inverse correlation between serum progesterone levels and fibroid ER concentration, using a ligand binding assay.…”
Section: Discussionmentioning
confidence: 75%